Diagnostic yield of 1000 trio analyses with exome and genome sequencing in a clinical setting - Malmgren, Helena; Kvarnung, Malin; Gustafsson, Peter; Anderlid, Britt-Marie; Arthur, Cecilia; Carlsten, Jonas; De Geer, Karl; Ehn, Emma; Grigelioniené, Giedre; Hammarsjö, Anna; Helgadottir, Hafdis T.; Hellström-Pigg, Maritta; et al. (Frontiers in Genetics, 2025)
IntroductionA trio analysis refers to the strategy of exome or genome sequencing of DNA from a patient, as well as parents, in order to identify the genetic cause of a disorder or syndrome.MethodsDuring the last 10 years, we have successfully applied exome or genome sequencing and performed trio analysis for 1,000 patients.ResultsOverall, 39% of the patients were diagnosed, with the detection of causative variant(s). The variants were located in 308 different genes. Autosomal dominant de novo variants were detected in 46% of the solved cases. Detection rates were highest in patients with a syndromic neurodevelopmental disorder (46%) and in patients with known consanguinity (59%). Even for patients previously analyzed as singletons, using a pre-defined gene panel, a consecutive trio analysis resulted in the detection of a causative variant in 30%.DiscussionA major advantage of trio analysis is the immediate identification of de novo variants as well as confirmation of compound heterozygosity. Additionally, inherited variants from a healthy parent can be dismissed as non-disease causing. The trio strategy enables analysis of a high number of genes–or even the whole genome–simultaneously. The strengths of a trio analysis, in combination with analysis of genome sequence data, allows for the detection of a wide range of genetic aberrations. This enables a high diagnostic yield, even in previously analyzed patients. Our current protocol for trio analysis is based on genome sequencing data, which allows for simultaneous detection of single nucleotide variants, insertion/deletions, structural variants, expanded short tandem repeats, as well as a copy number analysis corresponding to an array-CGH, and analysis regarding SMN1 gene copies.